2014 International Conference on Simulation of Semiconductor Processes and Devices (SISPAD) 2014
DOI: 10.1109/sispad.2014.6931553
|View full text |Cite
|
Sign up to set email alerts
|

3D multi-subband ensemble Monte Carlo simulator of FinFETs and nanowire transistors

Abstract: Abstract-In this paper we present the development of a 3D Multi Subband Ensemble Monte Carlo (3DMSB-EMC) tool targeting the simulation of nanoscaled FinFETs and nanowire transistors. In order to deliver computational efficiency, we have developed a self-consistent framework that couples a MSB-EMC transport engine for a 1D electron gas with a 3DPoisson-2DSchrödinger solver. Here we use a FinFET with a physical channel length of 15nm as an example to demonstrate the applicability and highlight the benefits of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This simulation scheme presents two main advantages with respect to the full-quantum approach: the first one is its affordable computational time and the second one is the inclusion of the quantum transport phenomena in a separate manner so that they can be switched ON and OFF to check their effect. Furthermore, despite the fact that the FinFET is a 3-D structure, this code can properly simulate it: a 2-D description (which assumes height much higher than thickness) can be appropriate for a FinFET with a sufficiently high aspect ratio [10].…”
Section: Methodsmentioning
confidence: 99%
“…This simulation scheme presents two main advantages with respect to the full-quantum approach: the first one is its affordable computational time and the second one is the inclusion of the quantum transport phenomena in a separate manner so that they can be switched ON and OFF to check their effect. Furthermore, despite the fact that the FinFET is a 3-D structure, this code can properly simulate it: a 2-D description (which assumes height much higher than thickness) can be appropriate for a FinFET with a sufficiently high aspect ratio [10].…”
Section: Methodsmentioning
confidence: 99%
“…In terms of subbands, the lowest energy was attained for in the planar transistor, whereas it shifted to in the vertical one. It is important to notice that, although the FinFET is a 3D structure and our simulation approach is 2D, it has been shown that FinFETs with fin heights much larger than their corresponding thicknesses show similar behavior in all transport regimes when using 2D and 3D simulations [ 10 ].…”
Section: Simulation Framework and Device Structuresmentioning
confidence: 99%
“…To model a non-planar device, such as GAA MOSFETs, we employ a simulator based on the MS-EMC approach. This method has been widely and successfully employed for the simulation of planar semiconductor devices [6,7,8,9], and only recently it has been applied to 3D devices [10,11]. The simulator is based on the space-mode approach [12], where the SE is solved in several cross sections perpendicular to the transport direction z, for each considered conduction band valley.…”
Section: Simulator Descriptionmentioning
confidence: 99%